Vibration effect on the corrosion rate of crude oil pipeline - Hadi Jasim, Haider (International Journal of Engineering and Technology, 2019)
In this paper, evaluation the influence of vibration on the corrosion rate of API 5L X60 and API 5L X80 carbon steel pipelines used for delivering of crude oils. A grouped of equipment are constructed laboratory and then used in the vibration-immersion corrosion test. The experimental results demonstrated that the vibration effects on crude oil properties and contribute to the dissociation of components of crude oils essentially water, dissolved gases and asphalt which leads to increase the corrosion rates compared to static case. The vibration process effect on the material compositions, i.e., the vibration effect on bonds between atoms of metal which leads to reduces of resistances of material to corrosion process.Â
Keywords: Chloride Salts; Trace Element; Vibration; Asphalt; CO2 and H2S Gases.